2020
DOI: 10.1182/blood-2020-137060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gain and Amplification of 1q in Newly Diagnosed Multiple Myeloma Patients Receiving Carfilzomib-Based Treatment in the Forte Trial

Abstract: Background Copy-number alterations of chromosome 1q are frequently found in multiple myeloma (MM) and are associated with poor prognosis. Recently, it has been demonstrated that the number of 1q copies correlates with a high-risk behavior (BA Walker et al, Leukemia 2019, TM Schmidt et al, Blood Cancer J 2019), but no data are available in carfilzomib-treated patients (pts). Here we aim at dissecting the role of Gain1q (3 copies of 1q) vs amplification 1q (Amp1q, ≥4 copies of 1q) in carfilzomib-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…However, the results regarding the outcome of patients with 1q21 amp have not been published yet [30]. On the other hand, encouraging results regarding patients with 1q21 gain have come from the FORTE trial [30]. The results from this study showed that NDMM patients who received carfilzomib in combination with cyclophosphamide and dexamethasone (KRd) prior to and after ASCT have a longer PFS while patients with 1q21 amplification showed a very poor response to the treatment [30].…”
Section: Pathogenesis and Clinical Implications Of 1q21 Amplificationmentioning
confidence: 87%
See 2 more Smart Citations
“…However, the results regarding the outcome of patients with 1q21 amp have not been published yet [30]. On the other hand, encouraging results regarding patients with 1q21 gain have come from the FORTE trial [30]. The results from this study showed that NDMM patients who received carfilzomib in combination with cyclophosphamide and dexamethasone (KRd) prior to and after ASCT have a longer PFS while patients with 1q21 amplification showed a very poor response to the treatment [30].…”
Section: Pathogenesis and Clinical Implications Of 1q21 Amplificationmentioning
confidence: 87%
“…A more recent retrospective study has shown that patients with 1q21 gain have a better response to VDT induction therapy and accomplish a very good response (VGR) and/or complete response (CR) after ASCT when compared to patients without 1q21 gain [29]. In addition to bortezomib, it has been proposed that carfilzomib, a novel second-generation PI, may be capable to overcome bortezomib resistance in high-risk MM patients [30]. Early-phase clinical studies have demonstrated that NDMM high-risk patients treated with carfilzomib-based induction achieved impressively high rates of MRD negativity and longer PFS.…”
Section: Pathogenesis and Clinical Implications Of 1q21 Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, patients with gain(1q) had worse survival in the KCd_ASCT and KRd12 arms, but the risk was abrogated in the KRd_ASCT arm. However, it was noted that patients with amp(1q) had dismal outcomes regardless of treatment arm, unless they were able to achieve negative minimal residual disease (MRD) 70 . More data regarding the outcomes of patients with and without +1q in Phase 3 clinical trials are compiled in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…They also found that Kaplan-Meier curves for OS were similar between patients with gain(1q21) and amp(1q21) until around 12 months after initiation of therapy, but clear separation in the curves was seen after 12 months. More recently, in a study by D’Agostino et al from the Forte trial including 474 NDMM patients treated with carfilzomib-based induction followed by ASCT [ 65 ], patients with amp(1q21) showed inferior PFS and OS compared to those with gain(1q21) (HR for PFS and OS: 1.8 and 3.1, p = 0.004 and <0.001, respectively). In a study by Ziccheddu et al with 42 patients refractory to both PIs and IMiDs [ 66 ], where 83% of patients expired within 1000 days of sampling, amp(1q21) was found in 45% of patients, and amp(1q21), but not gain(1q21), showed a significantly poor PFS and a trend towards worse OS compared to those with 2 or 3 copies of 1q21.…”
Section: Clinicopathological Features Of 1q21+ In MMmentioning
confidence: 99%